Maternal and neonatal outcomes of placenta increta and percreta from a multicenter study in China. (18th August 2019) - Zhang, Huijing; Dou, Ruochong; Yang, Huixia; Zhao, Xianlan; Chen, Dunjin; Ding, Yilin; Ding, Hongjuan; Cui, Shihong; Zhang, Weishe; Xin, Hong; Gu, Weirong; Hu, Yali; et al.
Abstract: Objective: The objective of this study is to identify the maternal and neonatal outcomes in women with placenta increta or placenta percreta in China. Materials and methods: We retrospectively analyzed 2219 cases from 20 tertiary care centers in China between January 2011 and December 2015. All cases were diagnosed of placenta increta or placenta percreta, based on either intraoperative findings or histopathological findings. Results: The incidence of placenta increta and placenta percreta progressively increased from 0.18% in 2011 to 0.78% in 2015. Compared with the placenta increta, placenta percreta was strongly related to serious adverse outcomes: postpartum hemorrhage (65.9% versus 38.6%, p  = .003), blood transfusion (86.2% versus 46.5%, p  < .001), hysterectomy (43.3% versus 11.2%, p  < .001), preterm birth (65.7% versus 49.9%, p  < .001), and the need for neonatal intensive care unit (NICU) admission (54.5% versus 36.7%, p  < .001). Conclusion: The incidence of placenta increta and placenta percreta is likely to increase in China. The depth of placenta implantation is associated with the severity of outcomes. Placenta percreta tends to have worse maternal and neonatal outcomes.